The acquisition of directives in North Saami - Ijäs, Johanna Johansen (Septentrio Academic Publishing, 2021)
This article examines the acquisition of directives in a North Saami-speaking child between the ages of 1;8 and 3;0. The research questions are: How does the child express directives linguistically? How does the acquisition of directives develop in this period? Is the use of directives influenced by the morpho(phono) logical structure of various verb forms? Are there any similarities between child speech and child-directed speech? The results show that the directives in both child speech and child-directed speech can be divided into four main groups: imperative sentences, indicative sentences, verbless sentences and infinitive forms. The child used different types of directives throughout the study period, but verbless sentences and indicative forms predominated initially. Imperative forms increased after age 2;0. These three types each constituted approximately one-third of the child’s directives. The child began to modify directives at around the age of 2½ years with aspectual derivational suffixes or modal particles, or both derivations and particles. Initially, the child used morphologically simpleinflectional forms, but later, morphological complexity did not appear to affect the choice of directive type. Over half of the adult’s directives were imperative sentences, and there were significantly fewer verbless sentences in child-directed speech than in child speech. Direktiiva lea cealkkus man ulbmil lea váikkuhit nuppi olbmo daguide. Artihkal guorahallá direktiivvaid oččodeami máná gielas agis 1;8–3;0, ja dutkanmateriála vuođđuduvvá ovtta máná ja su áhči spontána ságastallamiidda mat leat báddejuvvon lagabui 15 diimmu. Ságastallamiid transkripšuvnnat leat kodifiserejuvvon iešguđetlágan direktiivatiippaid mielde. Bohtosat čájehit ahte sihke máná ja váhnema direktiivvaid sáhttá juohkit njealljin váldojoavkun: imperatiivahámit, indikatiivahámit, vearbbahis direktiivvat ja infinitiivahámit. Mánná atná iešguđetlágan direktiivvaid olles materiálačoaggináigge, muhto álggus eanas vearbbahis direktiivvaid ja ...